THE ASSOCIATION OF INSOMNIA DEGREE WITH GRADE POINT AVERAGE PREDICATE IN STUDENTS OF THE FACULTY OF MEDICINE DUTA WACANA CHRISTIAN UNIVERSITY, YOGYAKARTA - Yulius Dennis Ariel; Venny Pungus; Ida Ayu Triastuti (Faculty of Medicine Universitas Kristen Duta Wacana, 2023)
Background Insomnia is the most common sleep disorder in the world. The incidence of insomnia in some medical students in Indonesia can also reach half of the population. Meanwhile, sleep is the phase where oxygen transport and neuron performance occur optimally. Objective This study aims to determine the association between the degree of insomnia and the grade point average predicate for Duta Wacana Christian University, Yogyakarta medical students. Methods The analytical study with a cross-sectional design was conducted in this research. The number of participants were 213 medical students from 2016, 2017, and 2018 batches who were taken randomly. The degree of insomnia data was taken by the insomnia severity index questionnaire. Results Through the questionnaire, 47.83% of male students and 39.67% of female students experienced sub-threshold insomnia, 7.6% of male students and 7.44% of female students experienced moderate-severity insomnia, and 0.82. % of female students have severe insomnia. Data were analyzed using Chi-square statistical test. Based on the results of the Chi-square analysis, the p-value obtained is 0.058 (p-value > 0.05) so the results are not in accordance with the hypothesis Conclusion It can be concluded from these results that the degree of insomnia does not associate with the grade point average predicate for medical students of Duta Wacana Christian University, Yogyakarta. Keywords: degree of insomnia, grade point average predicate, medical students